IMPLEMENTASI SISTEM INFORMASI MANAJEMEN TERHADAP EFISIENSI PROSES BISNIS IMPLEMENTATION OF MANAGEMENT INFORMATION SYSTEMS ON BUSINESS PROCESS EFFICIENCY - Kia Napisa Siregar; Muhammad Irwan Padli Nasution (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The implementation of Management Information Systems (MIS) is crucial for enhancing operational efficiency and effectiveness. Several key aspects in its implementation include: data collection, analysis and decision-making, process automation, improved communication to ensure all parties have access to the same information, performance monitoring, and, of course, data security. This research aims to examine the application of Management Information Systems in relation to business process efficiency. A qualitative approach is used, focusing on data collection through observation and analysis of the impacts of MIS. The implementation of MIS can significantly improve business process efficiency. The success of this implementation heavily depends on the right strategy, employee training, and ongoing management support. Regular evaluations are also necessary to ensure that the MIS continues to meet the organization’s needs. With a deep understanding and proper application, MIS can become an important asset in achieving competitive advantage and operational efficiency.